Cation templated improved synthesis of pillar[6]arenes. Issue 54 (16th May 2016) - Da Pian, M.; De Lucchi, O.; Strukul, G.; Fabris, F.; Scarso, A.
Abstract : Improved high yield syntheses of the larger pillar[6]arenes (P[6]) bearing different alkoxy substituents through cation templated syntheses using a series of small organic and organometallic cations is reported. Abstract : Improved high yield syntheses of the larger pillar[6]arenes (P[6]) bearing different alkoxy substituents through cation templated syntheses using a series of small organic and organometallic cations is reported. Yields of P[6] up to 38% and P[6]/P[5] ratios as high as 5 : 1 were achieved.